" Match Your Own Voice!": An Educational Tool for Vocal Training - Angelakis, Evangelos; Velianitis, Panayiotis; Andreopoulou, Areti; Georgaki, Anastasia (Audio Engineering Society Convention 143, 2017)
In this paper, we discuss the development and preliminary evaluation of a new educational tool, intended for novice and advanced vocal students. The software, written in Max / MSP, aims to assist singing practice by providing users with a visual substitute to their subjective auditory feedback. Under the guidance of their professional vocal instructor, students can store in the software spectral representations of accurately produced sounds, creating personalized Reference Sound Banks (RSBs). When students practice on their own, the software can be put into practice, assisting them to match their current Voice Spectrum Harmonic Content to the stored RSBs one note at a time. Results of a preliminary evaluation showed that, when using this software, students achieve a larger number of accurately produced sounds in a smaller amount of time.